Conceptual framework on risk-based supervision of Islamic Banks: a proposed risk-based supervisory framework - Suleiman Sani, Dalhatu; Sharofiddin, Ashurov (Smart Ever Konferans Organizasyon Limited Sirketi, 2020)
The main objective of this conceptual study is to propose an ideal risk-based supervisory framework for Islamic banks that recognises the specificities of Islamic banks. Thus, it gives a more accurate assessment of their financial health (risk profile) as opposed to using current conventional banking based frameworks to assess Islamic banks. The methodology adopted has been a qualitative approach through a critical in-depth review of literature related to the area of study based on available secondary data to generate valuable insights. The expected implication and contribution of the framework is that Islamic banks will be better supervised by regulators which will lead to safer Islamic banks and in turn promote the safety and soundness of the financial system at large. The study will also aid Islamic banks to better understand and manage the unique risks inherent in their line of business (Islamic banking). This paper also contributes to alleviating the current dearth of academic literature on the crucial regulatory subject of risk-based supervision in the Islamic finance industry.